The Causal Effect of Stock Market Development, Financial Sector Reforms and Economic Growth: The Application of Vector Autoregressive and Error Correction Model - Manasseh, Charles O.; Ogbuabor, Jonathan E.; Anumudu, Charles N.; Abada, Felicia C.; Okolie, Martins A.; Okoro, Okoro E. (International Journal of Economics and Financial Issues, 2018)
The study examined the causal relationship between stock market development, financial sector reform and economic growth in Nigeria, using Vector autoregressive and error correction model for the analysis. We observed bidirectional causality between stock market development and economic growth, along with financial sector reform and economic growth. This implies that stock market development and economic growth and; financial sector development and economic growth promote each other. More so, the findings reveal a unidirectional causality running from financial sector reform to stock market development. Hence, there is an evidence of positive long-run relationship between the variables of cointegrating equations. Furthermore, more inquiries on the relationship between business environment, legal framework and stock market development, show a positive long run relationship between the variables of the cointegrating vectors, suggesting that good business environment and quality legal framework could be a prerequisite for stock market development through confidence building and investors protection. Keywords: Economic Growth, Stock Market Development, Financial Sector Reform JEL Classifications: G10. EO2, E44